RESPON PERTUMBUHAN DAN HASIL TANAMAN KACANG TANAH (Arachis hypogaea L.) KULTIVAR KELINCI TERHADAP APLIKASI JENIS MULSA ORGANIK DAN PUPUK ORGANIK CAIR - Taffany, Jeaneva Dyena; Suciaty , Tety; Budirokhman, Dodi (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2024)
This study aims to determine the effect of the application of types of organic mulch and liquid organic fertilizer on the growth and yield of peanut (Arachis hypogaea L.) Rabbit Cultivar. The research was conducted in Bandorasakulon Village, Cilimus District, Kuningan Regency, in September – December 2023. The research method used was an experiment with a Randomized Group Design (RAK). The treatment tested was a combination between POC concentration (0 ml/liter of water, 20 ml/liter of water, and 40 ml/liter of water) and organic mulch (rice straw mulch and reed mulch). There were 9 treatment combinations that were repeated 3 times so that there were 27 experimental units. Observations were made on plant height, number of leaves, stem diameter, root length, plant growth rate, number of gynophores per plant, number of pods per plant, weight of 100 dry seeds, dry seed weight per plant and per plot. The data results were processed using analysis of variance with a linear model, if there were significant differences followed by using the Duncan cluster test. The results showed that the application of rice straw mulch and liquid organic fertilizer gave a significant effect on plant height, the number of leaves, stem diameter, number of pods per plant, weight of 100 dry seeds, and dry seed weight per plant and per plot. The highest yield was obtained in the combination treatment of rice straw mulch and 20 ml/l NASA liquid organic fertilizer, which was 785,40 grams/plot or equivalent to 2,61 tons/ha.